Black sails. The complete third season [videorecording (DVD)] - Sakharov, Alik, 1959-; Ettlin, Lukas, 1975-; Stephens, Toby, 1969-; New, Hannah; Arnold, Luke; Stevenson, Robert Louis, 1850-1894 (Starz, 2016)
With the help of the daughter of a local kingpin, Captain Flint and his men attempt to fight off the British Navy.